Hospital survival following pediatric HSCT: changes in complications, ICU therapies and outcomes over 10 years - Olson, Taylor L.; Pollack, Murray M.; Dávila Saldaña, Blachy J.; Patel, Anita K. (Frontiers in Pediatrics, 2023)
Introduction: Hematopoietic stem cell transplantation (HSCT) is an increasingly utilized therapy for malignant and non-malignant pediatric diseases. HSCT complications, including infection, organ dysfunction, and graft-versus-host-disease (GVHD) often require intensive care unit (ICU) therapies and are associated with mortality. Our aims were to identify the HSCT characteristics, complications and ICU therapies associated with (1) survival, and (2) survival changes over a ten-year period in a national dataset. Methods: A national sample from the Health Facts (Cerner Corporation, Kansas City, MO) database from 2009-2018 was utilized. Inclusion criteria were age 30 days to <22 years and HSCT procedure code. For patients with >1 HSCT, the first was analyzed. Data included demographics, hospital length of stay (LOS), hospital outcome, transplant type and indication. HSCT complications included GVHD and infections. ICU therapies were positive pressure ventilation (PPV), vasoactive infusion, and dialysis. Primary outcome was survival to discharge. Statistical methods included bivariate analyses and multivariate logistic regression. Results: 473 patients underwent HSCT with 93% survival. 62% were allogeneic (89% survival) and 38% were autologous (98% survival). GVHD occurred in 33% of allogeneic HSCT. Infections occurred in 26% of all HSCT. ICU therapies included PPV (11% of patients), vasoactive (25%), and dialysis (3%). Decreased survival was associated with allogeneic HSCT (p<0.01), GVHD (p=0.02), infection (p <0.01), and ICU therapies (p<0.01). Survival improved from 89% (2009-2013) to 96% (2014-2018) (p<0.01). Allogeneic survival improved (82% to 94%, p<0.01) while autologous survival was unchanged. Survival improvement over time was associated with decreasing infections (33% to 21%, p<0.01) and increasing vasoactive infusions (20% to 28%, p=0.05). On multivariate analysis, later time period was associated with improved survival (p<0.01, adjusted OR 4.28). Discussion: Hospital survival for HSCT improved from 89% to 96% from 2009 to 2018. Factors associated with mortality included allogeneic HSCT, GVHD, infections and ICU therapies. Improving survival coincided with decreasing infections and increasing vasoactive use.